PERILAKU KOROSI PADA SAMBUNGAN PLAT PEMBENTUK BODI MOBIL - Arbintarso, Ellyawan Setyo (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
Effect of plate joint on automobile body which susceptible to corrosion has been investigated also corrosion rate on automobile plate when the coating has impacted. Rain and sea water was used as corossion medium as normally affected on automobile plate. Low carbon steel has been choosed as standart plate. The forming of plate as a joint which folding and welding used a standart manufacture of automobile industry. The re-sults have shown the losses weight of plate faster on the sea water environment. After immersed in the sea water for 627 hours the corrosion rate of folding plate joint has 0.000806 mpy, although it was at a standstill outstanding level. Coating paint can decrea-sed 20% corrosion rate, but still need attention to care if the automobile body was impac-ted.